Perbedaan Saham dan Sertifikat Modal Koperasi Ditinjau Dari Kajian Yuridis Menurut Hukum Koperasi Indonesia - Nugraha, Agus Bambang (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This review aims to analyze between cooperative and share capital certifications so that they can be used as one of the rules in deciding their decision to contribute. The type of research used is a research setting that refers to the legal norms contained in the law, as well as important exploratory information consisting of books, laws and guidelines, diaries, articles and others. The data collection procedure used in this exploration is a literature study. Guidelines regarding capital certification itself are contained in Law Number 17 of 2012 concerning Cooperatives, while guidelines regarding shares can be found in Law Number 40 of 2007 concerning Limited Liability Companies. The consequence of the review shows that there are three important differences between support and beneficial offerings of capital which can be seen from the importance, granting of voting rights and shifting of responsibilities for declarations and offerings of capital. Thus, it is believed that there will be outreach to the public in general through socialization about the difference between the declaration of certificated capital and shares, so that it becomes material for thinking for the wider community in making business, both in cooperatives and in limited liability companies.